SUPPORTING FACTORS FOR PERSONAL FINANCIAL MANAGEMENT OF PERSONNEL OFFICE OF THE AGRICULTURAL MUSEUM IN HONOR OF HIS MAJESTY THE KING (PUBLIC ORGANIZATION) - Panphadung, Suparut; Poompruk, Chanattee (RMUTT Global Business and Economics Review, 2023)
Academic Article on Supporting Factors in Personal Financial Management of Personnel of the Office of the Agricultural Museum in Honor of His Majesty the King (Public Organization) prepared from studies, research and conclusions obtained from data collection from knowledge sources on published databases. Academic articles, journal articles, books, textbooks and research related to wise personal financial management. To be a guideline for effective living Have stability in personal financial management However, individual financial management may have different methods as appropriate. which can study more information in order to know which type of financial management is suitable for themselves and it can also be a guideline for financial planning in the future.